Relevance and Application of Compulsory Health Insurance in Republic of Uzbekistan - Ortiqov Obod Khudaybergan ogli (Scientific Trends, 2023)
The main features of the health sector - its colossal social significance and availability of guaranteed legislative norms of the state for number of basic health services to population of particular country. The enormous social importance of the healthcare sector and active state regulations completed the medical services market, need for professional intermediaries capable of qualitatively defend the rights of patients. Such, as a rule, are insurance organizations. As the world experience demonstrates, medical insurance (both voluntary and compulsory) is able to play a very positive role in improving the quality of medical services, by attracting additional resources to the health sector, protecting interests and rights of wide sections of the population. In Uzbekistan, this insurance industry is still at its initial stage development. There are a number of problems that prevent a wider dissemination of this type of insurance services. Studying the problems and features of the market and appropriate recommendations with innovative ideas for development is the main purpose of this paper.
Keywords: compulsory and voluntary health insurance, healthcare, international experience.